IMPLEMENTASI BPJS KESEHATAN DALAM UPAYA REFORMASI JAMINAN KESEHATAN MENUJU UNIVERSAL HEALTH COVERAGE DALAM PERSPEKTIF EKONOMI SYARI’AH. (STUDI KASUS PADA BPJS KESEHATAN KOTA BANDAR LAMPUNG) - abizar, abizar (Mu'amalatuna: Jurnal Ekonomi Syariah, 2019)
Social security is "at-takaful al-ijtima`i" which is defined as solidarity and mutual assistance to help among communities, both individuals and collectives and the role of the state to take positive steps with Islamic motivation. This meaning is in harmony with what has been determined by Al-Qur ʻan Al-Maidah Verse (2). Islam commands the state to guarantee the collective needs of the people without distinguishing between rich and poor with halal corridors. Indonesia needs a development approach that not only pursues economic growth, but is oriented towards aspects of social protection and poverty alleviation. Social security is essentially a protection strategy to sustain and maintain economic stability. BPJS Health was formed to organize the National Health Insurance program. Social security reform is expected to reach Universal Health Covarage. This research seeks to answer and examine the formulation of the problem namely; how is the implementation of Health Insurance reform towards Universal Health Coverage in Bandar Lampung in the Shariah Economic Perspective? . This research belongs to field research and is a qualitative descriptive research. The results showed that the implementation of Health Insurance reform towards Universal Health Coverage in Bandar Lampung City was not in accordance with sharia economic principles and principles. Based on the results of this study, it is recommended to conduct an academic study on the Concept of Social Security in Indonesia which is based on the perspective of Sharia Economy.